Double blind comparison of omeprazole (40 mg od) versus cimetidine (400 mg qd) in the treatment of symptomatic erosive reflux oesophagitis, assessed endoscopically, histologically and by 24 h pH monitoring. Issue 5 (May 1990) - Dehn, T C; Shepherd, H A; Colin-Jones, D; Kettlewell, M G; Carroll, N J
Abstract : This double blind, double dummy study compares the rate of healing of erosive reflux oesophagitis, assessed endoscopically, with four and eight weeks treatment using omeprazole or cimetidine, and the effect of four and eight weeks treatment of reflux oesophagitis with omeprazole or cimetidine on reflux symptoms, microscopic healing, and in a subgroup of patients, oesophageal pH measurements. Omeprazole 40 mg once daily achieves (i) greater and more rapid symptom relief, (ii) more rapid and sustained endoscopic and histological healing, and (iii) greater reduction of oesophageal acid exposure than cimetidine 400 mg four times daily.